Evaluating parental personal utility of pediatric genetic and genomic testing in a diverse, multilingual population - Priya N. Marathe; Sabrina A. Suckiel; Katherine E. Bonini; Nicole R. Kelly; Laura Scarimbolo; Beverly J. Insel; Jacqueline A. Odgis; Monisha Sebastin; Michelle A. Ramos; Miranda Di Biase; Katie M. Gallagher; Kaitlyn Brown; et al. (HGG Advances, 2024)
Summary: There is increasing evidence of the clinical utility of genetic and genomic testing (GT); however, factors influencing personal utility of GT, especially in diverse, multilingual populations, remain unclear. We explored these factors in a diverse cohort of parents/guardians (participants) whose children received clinical GT through the NYCKidSeq program. A total of 847 participants completed surveys at baseline, post-results disclosure, and 6 months (6m) post-results. The largest population groups were Hispanic/Latino(a) (48%), White/European American (24%), and Black/African American (16%). Personal utility was assessed using the Personal Utility (PrU) scale, adapted for pediatric populations and included on the surveys. Three PrU subscales were identified using factor analysis: practical, educational, and parental psychological utility. Overall personal utility summary score and the three subscales significantly decreased after receiving results and over time. Hispanic/Latino(a) participants identified greater overall personal utility than European American and African American participants at all time points (p < 0.001) as did participants whose children received positive/likely positive results compared with those with negative and uncertain results (post-results: p < 0.001 and p < 0.001; 6m post-results: p = 0.002 and p < 0.001, respectively). Post-results, higher subscale scores were associated with lower education levels (practical, parental psychological: p ≤ 0.02) and higher levels of trust in the healthcare system (practical, parental psychological: p ≤ 0.04). These findings help to understand the perspectives of diverse parents/guardians, which is critical to tailoring pre- and post-test counseling across a variety of populations and clinical settings.